Research of Dynamics Modeling and Simulation of Rigid-flexible Coupled Parallel Robot - Wang Linjun; Shi Baozhou; Zhang Dong; Ding Shihao; Liu Jianming (Jixie chuandong)
There are elastic deformation and rigid-flexible coupling effects in the motion of parallel mechanism, which have great influence on the motion and stability of the mechanism. Aiming at the above problems, taking the 3-DOF rigid-flexible coupled parallel robot as research object， based on linear MSTMM， the multi-body system model and topological structure model of rigid-flexible coupled robot are established, and the spatial transformation equation and dynamics equation of the whole system are derived. Then the simulation model of robot SimMechanics is established by Matlab software, and the trajectory tracking of the robot is simulated based on PID control strategy. The simulation results show that the actual trajectory of the robot is in good agreement with the expected trajectory, and the system motion is stable. Thus the correctness and effectiveness of the modeling method are verified， a theoretical basis for further research on the parallel mechanism is provided.